From Criticism to Collaboration: Assessing the Police Reform from the Public’s Perspective and Its Management Implications - Vita Mayastinasari; Novi Indah Earlyanti; Rahmadsyah Lubis; Syafruddin (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Reform of the Indonesian National Police since its separation from the Indonesian National Armed Forces in 1999 has become a strategic agenda in the consolidation of democracy. Transformation efforts through various programs, from Bureaucratic Reform to the Precision Police vision, aim to build a professional, transparent, and accountable institution. However, public perception of Polri performance remains fluctuating, evident in the paradox between the public’s need for security and increasing criticism related to corruption, discrimination, and human rights violations. This study aims to analyze Polri reform from the public’s perspective, assess the transition from criticism to collaboration, and identify forms of criticism and patterns of collaboration. The method used is a qualitative constructivist paradigm with a literature study approach and secondary data analysis from CSO reports, public opinion surveys, and the media. The findings indicate that digital service innovation is appreciated by the public, but integrity and accountability remain weaknesses, resulting in criticism continuing to emerge as indicators of legitimacy erosion. In conclusion, internalizing procedural justice, building social legitimacy, and consistent dialogic communication are key to transforming criticism into a strategic partnership between Polri and the public.